The Influence of Motivation, Achievement, Work Experience and Competencies on the Performance of Mental Nurses - Livana PH; Desmon Desmon; Yudhinanto Yudhinanto; Maria Septijantini Alie; Eka Travilta Oktaria (GLOBAL HEALTH SCIENCE GROUP, 2024)
Performance in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Factors that can influence performance are motivation, competence, leadership, achievement, work environment and work experience. The aim of this research was to determine the influence of motivation, achievement, work experience and competency on the performance of nurses at RSJD Dr Amino Gondohutomo, Central Java Province. The method used in this research was quantitative descriptive, the number of samples used was 71 respondents from part of the existing population which had been obtained using the Slovin technique. The results of this research showed that the four variables of motivation, achievement, work experience and competence simultaneously influenced the performance of nurses at RSJD Dr Amino Gondohutomo, Central Java Province. The results of the motivation variable partially influence the performance of nurses at RSJD Dr Amino Gondohutomo, Central Java Province. The results of the achievement variable partially influence the performance of nurses at RSJD Dr Amino Gondohutomo, Central Java Province. The results of the work experience variable partially influence the performance of nurses at RSJD Dr Amino Gondohutomo, Central Java Province. The results of the competency variable partially influence the performance of nurses at RSJD Dr Amino Gondohutomo, Central Java Province. Suggestions are expected to use other independent variables, for example education, work discipline, wages, leadership, workload and so on.